2015
DOI: 10.7196/samj.8696
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in non-communicable diseases in South African primary healthcare

Abstract: Corresponding author : R Mash (rm@sun.ac.za) Background. Multimorbidity in non-communicable diseases (NCDs) is a complex global healthcare challenge that is becoming increasingly prevalent. In Africa, comorbidity of communicable diseases and NCDs is also increasing. Objectives. To evaluate the extent of multimorbidity among patients with NCDs in South African (SA) primary healthcare (PHC). Methods. A dataset obtained from a previous morbidity survey of SA ambulatory PHC was analysed. Data on conditions cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 16 publications
(27 reference statements)
4
89
1
Order By: Relevance
“…[4] A more recent survey of SA PHC found that 18% of patients with hypertension also had diabetes, and 63% of patients with diabetes also had hypertension. [3] Our study demonstrated higher levels of comorbidity than these studies, with 47% of participants with hypertension also having diabetes, and 84% of participants with diabetes also having hypertension. A study of urban SA women demonstrated high rates of comorbid psychological distress with physical disease, [13] consistent with our finding of 51% of participants with hypertension, diabetes or chronic respiratory disease also having symptoms of depression.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…[4] A more recent survey of SA PHC found that 18% of patients with hypertension also had diabetes, and 63% of patients with diabetes also had hypertension. [3] Our study demonstrated higher levels of comorbidity than these studies, with 47% of participants with hypertension also having diabetes, and 84% of participants with diabetes also having hypertension. A study of urban SA women demonstrated high rates of comorbid psychological distress with physical disease, [13] consistent with our finding of 51% of participants with hypertension, diabetes or chronic respiratory disease also having symptoms of depression.…”
Section: Discussioncontrasting
confidence: 47%
“…A recent cross-sectional survey of reasons for consultations in PHC in four SA provinces confirmed that management of hypertension was the most common reason for attendance, with NCDs accounting for 14% of visits. [2,3] …”
mentioning
confidence: 99%
“…Two articles in this issue address comorbidity and multimorbidity in NCDs in the SA setting, [8,9] the former suggesting that future clinical guidelines, training of primary care nurses and involvement of doctors in the continuum of care should address the complexity of patients with NCDs and multimorbidity, and the latter warning against mobilisation of scarce resources to implement mass screening for diabetes and hypertension in the absence of adequate evidence of benefit.…”
Section: Noncommunicable Diseases (Ncds)mentioning
confidence: 99%
“…All articles submitted to all the HMPG titles are 'seen' by the iThenticate plagiarism screening system, which screens submitted papers for originality and can tell whether a paper contains passages of text that also appear in other publications or resources. [8] This means that we can (generally, but not always) catch articles with plagiarised content.…”
mentioning
confidence: 99%
“…Ideally, the core services would be delivered by a multidisciplinary team (MDT) which consists of the doctor, nurse, physiotherapist, occupational therapist and dietician, all focusing on their respective areas of expertise. However, the primary health care (PHC) system in South Africa, especially in the rural areas, is not readily equipped with full time MDTs, and patients are often only seen by one or two of the members in the team (Bateman, 2012;Lalkhen and Mash, 2015). In addition, underutilisation of rehabilitation services and the lack of adherence to evidence-based guidelines is a concern previously found in PHC settings of South Africa for patients suffering from musculoskeletal disorders (Major-Helsloot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%